Education on Efforts to Maintain Teenagers' Mental Health Due to Academic Burden and Social Pressure at SMAN 6 Tangerang Regency - Dwi Nurmawaty; Santos Winarso Dwiyogo (Abdimas Paspama, 2025)
The adolescent stage is a stage where a person gets a burden in the form of new responsibilities and demands from the surrounding environment. Some experts state that adolescents are very vulnerable to experiencing mental or psychological problems. Adolescents who are also students often experience stress due to social pressure and demands in the school environment. A survey conducted by the Indonesia-National Adolescent Mental Health Survey (I-NAMHS) in 2022, stated that there were around 15.5 million or 34.8% of adolescents in Indonesia who experienced mental health problems. This counseling was conducted to minimize academic stress in adolescents by creating healthy competition in the school environment, by presenting an understanding of what mental health is, its impact, and efforts that can be made to maintain adolescent mental health. This counseling was conducted using lecture and question and answer methods involving 35 students of SMAN 6 Tangerang Regency. Knowledge measurement or evaluation was carried out using pre-test and post-test questions for students. The results of the pre-test and post-test questions done by students can be an indicator that the counseling activities carried out are quite effective because there is an increase in knowledge in students related to the definition of mental health and efforts that can be made to maintain mental health. After this counseling, it is expected that no student of SMAN 6 Tangerang Regency will experience mental health problems.